Examining caregiver-adolescent symptom agreement and its influence on treatment outcomes: a quantitative analysis - Kroll, Elizabeth; Hessdorf, Sara; Brandis, Alyson; Kanopka, Klint; Kohlmeier, Jonathan; Heard, Hannah; Zant, Izabella; Stolzenbach, Stephanie; Fenkel, Caroline (Frontiers in Psychology, 2025)
IntroductionCaregivers play a critical role in identifying and interpreting adolescent mental health symptoms, yet their perceptions often differ from those of adolescents themselves. Such discrepancies can influence treatment engagement and outcomes, making it essential to understand the factors that affect caregiver–adolescent agreement in symptom reporting.MethodsThis study analyzed baseline depression and anxiety symptom reports from 763 caregiver–adolescent dyads enrolled in a virtual intensive outpatient program. Agreement between adolescent self-reports and caregiver proxy reports was assessed using concordance analyses. Potential moderators included adolescent age, gender identity, race, neurodivergence, caregiver well-being, and family functioning. Additional analyses examined whether agreement predicted treatment outcomes, including symptom improvement and treatment completion.ResultsOverall, caregiver–adolescent agreement was low to moderate (CCC = 0.215). Adolescents identifying as non-binary showed the largest discrepancies, typically rating their symptoms as more severe than their caregivers. Higher family functioning was associated with reduced directional disagreement for depression, though this pattern did not hold for anxiety. Dyads in which caregivers reported higher symptom severity than adolescents demonstrated greater symptom improvement by discharge, while agreement levels did not significantly predict treatment completion.DiscussionInformant discrepancies were common and clinically meaningful, particularly among gender-diverse adolescents and families reporting lower functioning. Although overall agreement did not predict treatment completion, caregiver perceptions of greater symptom severity were linked to greater reductions in adolescent depression and anxiety over treatment. These findings suggest that incorporating caregiver perspectives into assessment and treatment planning may enhance outcomes, especially in high-acuity virtual care settings. Future research should investigate mechanisms through which caregiver engagement influences adolescent symptom change over time.